Rancang Bangun Absensi Elektronik Berbasis Mikrokontrolller Atmega328 - Subandi Saputra; Aswardi Aswardi (invotek, 2018)
This paper aims to update the conventional attendance system. The focus of this final assignment is: (1) Creating an electronic attendance machine with biometric sensor based on Microcontroller Atmega328, (2) Renewing conventional attendance method into digital absence, and (3) Determining employee performance based on absenteeism. In making of this final task, the writer uses microcontroller atmega328 as main control center, fingerprint reader as main input, LCD as time information viewer on real time clock circuit, and series of SD card module as database system used to store information at the time of absences. Based on the results of the testing of the design of electronic attendance based on atmega328 microcontroller is as follows, the first can be used as a substitute for conventional absorption taking system. This is because the tool is equipped with fingerprint reader sensor so that in absenteeism cannot be represented. In addition, this tool also has been equipped with RTC as a timer system that will record the delay of each user on this tool. the second process of taking attendance (reviewer) can only be done after the user perform the registration process.